Efforts to Detect Suspected Pulmonary Tuberculosis Cases Challenges and Strategies - Oxalis, Siti Chalista Zaisha; Sugianti, Ratna; Kusdiyah, Erny (Scientific Of Environmental Health and Diseases, 2025)
Background: Early detection of suspected pulmonary tuberculosis (TB) cases is essential to reduce transmission and improve treatment outcomes. However, case detection efforts at the community level may be limited by various individual and service-related factors. Objective: This study aimed to analyze factors associated with efforts to detect suspected pulmonary TB cases in the working area of Olak Kemang Public Health Center in 2024. Methods: An analytical observational study with a cross-sectional design was conducted among 120 respondents living in the health center coverage area. Data were collected using a structured questionnaire covering sociodemographic characteristics and factors related to TB suspected-case detection efforts. Univariate analysis was used to describe respondent characteristics, and bivariate analysis using the Chi-square test was applied to assess the association between independent variables and detection efforts, with a significance level of p < 0.05. Results: The majority of respondents were female (62.5%) and aged 25–44 years (48.3%). Bivariate analysis showed that education level (p=0.006), exposure to TB-related information (p=0.001), knowledge about TB (p<0.001), attitude toward TB screening (p<0.001), access to health services (p=0.002), and perceived stigma (p<0.001) were significantly associated with efforts to detect suspected pulmonary TB cases. Meanwhile, sex (p=0.458) and age (p=0.291) were not significantly associated with detection efforts. Conclusion: Efforts to detect suspected pulmonary TB cases were strongly influenced by modifiable factors including education, information exposure, knowledge, attitude, service accessibility, and stigma. Strengthening TB health education, expanding community outreach, improving access to services, and reducing stigma are recommended to enhance early detection and support TB control programs.